Thermo-Diffusion Effect on MHD Flow of Various Nano Fluids Past a Vertical Porous Plate - Babu, D. Dastagiri; Raju, M. C.; Venkateswarlu, S.; Reddy, E. Keshava (Communications in Mathematics and Applications, 2023)
An analytical model is employed for the nanofluid flow, heat and mass transfer from an infinite vertical plate in the presence of chemical reaction, and Soret effect. The governing equations that come from this are non-dimensionalized, transformed into a comparable form, and then solved using the three term perturbation technique and the accompanying boundary conditions. For this investigation, three different types of nano-fluids containing metallic nano particles as Cu (copper), and non-metallic nano particles as Al2O3 (alumina oxide), TiO2 (titanium oxide) are considered, and water is considered as a base nanofluid. Using the MATLAB “Perturbation Method” and the findings already published in the literature, the resulting results are verified. It is described how important variables including the magnetic parameter, chemical reaction parameter, Soret number, the solid volume percentage of nanoparticles, the kind of nanofluid used, Nusselt number, Sherwood number and skin friction coefficient affect the flow. Tabular comparisons with published findings are shown.